Sex without crossing over in the yeast Saccharomycodes ludwigii - Papaioannou, Ioannis A.; Dutreux, Fabien; Peltier, France A.; Maekawa, Hiromi; Delhomme, Nicolas; Bardhan, Amit; Friedrich, Anne; Schacherer, Joseph; Knop, Michael (Genome biology, 2021)
Intermixing of genomes through meiotic reassortment and recombination of homologous chromosomes is a unifying theme of sexual reproduction in eukaryotic organisms and is considered crucial for their adaptive evolution. Previous studies of the budding yeast species Saccharomycodes ludwigii suggested that meiotic crossing over might be absent from its sexual life cycle, which is predominated by fertilization within the meiotic tetrad.
Gesehen am 14.12.2021